Reimagining Cross-Border Cooperation From Indonesia-Malaysia Experiences: A Thematic Literature Review - Raharjo, Sandy Nur Ikfal; Idris, Hanizah (JAS (Journal of ASEAN Studies), 2025)
The research aimed to explore the scientific discourse of cross-border cooperation in Southeast Asia, particularly on the Indonesia-Malaysia border area. Through thematic literature review, this research collected and analyzed journal articles, books, book chapters, and doctoral dissertations. The literature review find the gaps in literatures on cross-border cooperation which focus more on physical connectivity on land border area with less attention to institutional and people-to-people dimensions. This research also shows that Indonesia-Malaysia and Southeast Asia in general pose a less-structured and informal form of cross-border cooperation, which is different with an institutionalized and formal form of cross-border cooperation posed by Euroregion. The literature review also synthesizes new insights to the existing cross-border cooperation understanding. These insights shows that cooperation can address various purposes in complement to socio-economic sector, can be expanded to include subnational, national, subregional level, and should adopt more inclusive goals by considering the interests of all parties involved and affected.